Analisis Proses Identifikasi Kebutuhan Pembelajaran Siswa Kelas 3 SD Negeri Cikokol Kota Tangerang - Magdalena, Ina; Oktapiani, Rizka; Salshabila, Saffana Rizka (Lembaga Yasin AlSys, 2023)
Needs analysis is an important stage that is carried out at the beginning of the learning process. This study aims to analyze the learning needs of grade 3 students at SD Negeri Cikokol. The design of this research is descriptive qualitative. The information needed in this study was obtained from observation and interviews. The respondent in answering is the third grade teacher. The stages in the needs analysis are observing the teacher's learning and teaching process in the classroom, and conducting interviews with teachers. The results of this study are in the form of a report on the learning needs of grade 3 students at SD Negeri Cikokol which shows that students need more digital teaching materials in the form of modules so that they can support learning activities. The results of this study are expected to be a reference for teachers and schools as material for consideration in carrying out teaching and learning processes that suit the needs of students.